Learning curves and collaboration in reconceiving refugee settlements - Cuéllar, M; Surendra, A (Refugee Studies Centre, University of Oxford, 2014)
A collaboration between UNHCR, Ennead Architects and Stanford University uses settlement design to promote innovation and further development in the refugee protection model but collaborators initially face a steep learning curve.